Level of physical activity in college students - Filho, Elias Benício de Luna; Silva, Fábio Thiago Maciel da; Santos, Amilton da Cruz; Nascimento, Leone Severino do; Rabay, Aline Nóbrega; Dantas, Filipe Fernandes Oliveira; Lima, Anna Myrna Jaguaribe de; Brasileiro-Santos, Maria do Socorro (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: Regular practice of physical activity is important to prevent and treat psychobiological dysfunctions and improve the quality of life. Insufficient levels of exercise have been considered a risk factor for diseases, mainly cardiovascular disorders. The evidences about the levels of physical activity in college students are inconsistent, especially in physical education undergraduate programs. Objective: The aim of this study was to assess the level of physical activity in Physical Education college students of the Universidade Federal da Paraíba, considering gender, undergraduate program (degree or bachelor) and term time. Method: The study design is transversal, and 159 subjects answered the International Physical Activity Questionnaire (IPAQ), short version. Results: Most of the college students were classified as active and very actives (77.4%) and, only 22.7% were insufficiently actives. It was observed a significant association between the level of physical activity and the term time (p=0.001), with a linear and progressive trend to towards an increase in the number of inactive/insufficiently active students. There was not significant association (p=0.088) between the level of physical activity and the first or second half of the undergraduate program. College’s Bachelor students of were more active than college’s Licentiate students, however, without significant association (p=0.181). In the difference between genders, women have higher levels of physical activity than men, but without significant association (p=0.797). Conclusion: The results show that students of physical education present appropriate levels of physical activity and students of the last term time are less active than first term time students.